2012
DOI: 10.1093/infdis/jir850
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of a Recombinant Simian Adenovirus ChAd63: A Potent New Vaccine Vector

Abstract: Background. Vaccine development in human Plasmodium falciparum malaria has been hampered by the exceptionally high levels of CD8+ T cells required for efficacy. Use of potently immunogenic human adenoviruses as vaccine vectors could overcome this problem, but these are limited by preexisting immunity to human adenoviruses.Methods. From 2007 to 2010, we undertook a phase I dose and route finding study of a new malaria vaccine, a replication-incompetent chimpanzee adenovirus 63 (ChAd63) encoding the preerythrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
234
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(266 citation statements)
references
References 26 publications
27
234
1
4
Order By: Relevance
“…No data on cellular responses to this antigen have been reported following natural P. falciparum infection; however, given that vaccination elicited peptide-restimulated responses spanning the entire RH5 sequence, the RH5_FL molecule does not appear to lack T cell epitopes. The kinetics and magnitude of the response were also similar to those previously reported following human vaccination with the same vectors encoding P. falciparum or P. vivax antigens (36)(37)(38)(39)43). Similarly, studies using chimpanzee adenovirus vectors followed by MVA boost (44,46,58) have routinely shown that a mixed antigen-specific CD4 + /CD8 + T cell response is induced in humans.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…No data on cellular responses to this antigen have been reported following natural P. falciparum infection; however, given that vaccination elicited peptide-restimulated responses spanning the entire RH5 sequence, the RH5_FL molecule does not appear to lack T cell epitopes. The kinetics and magnitude of the response were also similar to those previously reported following human vaccination with the same vectors encoding P. falciparum or P. vivax antigens (36)(37)(38)(39)43). Similarly, studies using chimpanzee adenovirus vectors followed by MVA boost (44,46,58) have routinely shown that a mixed antigen-specific CD4 + /CD8 + T cell response is induced in humans.…”
Section: Discussionsupporting
confidence: 80%
“…This heterologous prime-boost approach has shown antibody induction against difficult-to-express malaria antigens in numerous animal models, including nonhuman primates (32,34,35). These vectors, delivering antigens from P. falciparum, have now been shown to be safe and immunogenic for T cell and antibodies in healthy European and American adult volunteers (36)(37)(38)(39)(40), as well as African adults, children, and infants (41,42). More recently, similar adenovirus-poxvirus vectored vaccine technologies have been used to immunize humans against numerous other pathogens including P. vivax malaria (43), Ebola virus (44), hepatitis C virus (HCV) (45), respiratory syncytial virus (RSV) (46) and HIV-1 (47).…”
Section: Introductionmentioning
confidence: 99%
“…ecombinant adenoviruses (Ads) are currently being explored as candidate vaccine vectors for multiple pathogens (1)(2)(3)(4)(5)(6), as a result of their safety profile, manufacturability, and ability to induce broad and strong immune responses (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Multiple human and chimpanzee adenovirus vectors have been developed to date (8,9,(11)(12)(13).…”
mentioning
confidence: 99%
“…The recent addition of a chimpanzee adenovirus 63 (Ch"d63) for priming has provided encouraging results (see Table ). "dCh63 priming elicits both CD + and CD8+ T cells at much higher levels than DN" or FP9 priming [211], and also results in a much higher proportion of IFN-γ-secreting monofunctional CD8+ T cells that were correlated to sterile protection [212]. This combination has provided protection from infection in malarianaive volunteers comparable to the immunity provided by CSP using the same delivery platform [212,213].…”
Section: Me-trapmentioning
confidence: 92%